Electronic properties of single-walled carbon nanotubes in solar cells and conjugated polyelectrolyte composites - Li, Yao (2015)
As a novel nanomaterial with remarkable electronic properties, carbon nanotube (CNT) has been thought to be a candidate material for next-generation electronics and composite materials. The good mobility of SWNTs has shown to improve charge transport in dye-sensitized solar cells (DSSCs) and augment the device performance when SWNTs are incorporated in the TiO2 photoanodes. It has also been demonstrated that CNT can be well dispersed by CPEs in inorganic solvent without using surfactant. For application, the SWNT dispersion with the non-conductive CPE is implemented as electron transport layer (ETL) in organic photovoltaics (OPVs), and dispersion with the conductive CPE is made into a stable, conductive composite film. As ETL in OPVs, SWNTs enhance the charge transport from active layer to metal electrode and make the charge collection more efficient. In the CPE composites, by varying the SWNT concentrations the CPE/SWNT composite films can be tuned in terms of thickness, conductivity, and transmittance while retaining the intrinsic properties of CPEs.